Cooperative effects of immune enhancer TPPPS and different adjuvants on antibody responses induced by recombinant ALV-J gp85 subunit vaccines in SPF chickens. Issue 12 (14th March 2017) - Li, Yang; Meng, Fanfeng; Cui, Shuai; Fu, Jiayuan; Wang, Yixin; Cui, Zhizhong; Chang, Shuang; Zhao, Peng
Highlights: For the first time we applied the immune enhancer TPPPS in ALV-J gp85 subunit vaccine. We have studied and compared ALV-J gp85 protein vaccine plus different adjuvants combined with TPPPS systematicly. The vaccine could induce high-titre antibodies and maintain for a longer duration in the TPPPS-immunized group. The protection by maternal antibodies against ALV-J infection in the TPPPS-immunized group was better. Abstract: To explore the antibody responses and protective effects induced by subgroup J avian leukosis virus (ALV-J) gp85 protein vaccine plus different adjuvants (CpG and white oil adjuvant YF01) combined with the immune enhancer Taishan Pinus massoniana pollen polysaccharide (TPPPS), we immunized SPF chickens with the recombinant ALV-J gp85 protein, along with different adjuvants and immune enhancer, which protected the chickens by inducing different levels of protective antibodies. Results showed that a single injection of gp85 recombinant protein could only produce low-titre antibodies that were maintained over a short time in few chickens. When combined with YF01 or CpG adjuvants, the recombinant protein could induce high-titre antibodies in most of the immunized chickens. Moreover, when the immune enhancer TPPPS was used with the two adjuvants, it further elevated the antibody levels for a longer duration. The eggs from four groups with the highest levels of ALV-J antibodies were collected, hatched, and examined for maternal antibodies. The protection by the maternal antibodies against ALV-J infection in the TPPPS-immunized group was higher than that in the group without TPPPS, which was consistent with the observations in the parents. This study shows that the immune enhancer TPPPS, combined with YF01 or CpG adjuvants, can enhance the immunogenicity of gp85 recombinant proteins, and provide a better immuno-protection. It provides a powerful experimental basis for the development of ALV-J subunit vaccine. Efficient subunit vaccine development will also accelerate the process of purification of ALV-J.